AFTER SALE SERVICE DAN REPEAT PURCHASE INTENTION PADA PENGGUNA NISSAN DI FACEBOOK - Ubaidilah, Muhamad Rizki; Rahayu, Agus; Utama, Dian Herdiana (Journal of Business Management Education (JBME), 2018)
Objective - The purpose of this study is to determine the effect of after sale service to repeat purchase intention nissan users on facebook. Design / methodology / approach - The design of this study is cross sectional. This research use explanatory survey method. A total of 51 respondents were selected using probability sampling in the form of Cluster random sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is descriptive technique by using frequency distribution and verification technique by using simple linear regression analysis. Findings - Based on the results of research using analysis of verifikatif analysis, obtained the result that After sale service has a positive influence on repeat purchase intention with the influence of being. Originality / value -The difference of this research with previous research is located on the object of research that is Nissan User Â on Facebook, with variables studied that is After Sale Service and Repeat Purchase Inention, and use theory or reference different from previous researcher.